FACTORS OF FORMATION AND SPECIAL TYPOLOGY OF INPUT GROUPS OF BUILT-IN SERVICE COMPANIES - Кулик, А. В.; Швець, І. В.; Абизов, В. А. (Art and Design, 2021)
Purpose: to identify the peculiarities of the formation and typology of incoming groups of built-in service enterprises. The methodology consists in the application of general scientific methods of analysis, synthesis, comparative analysis, as well as in the formation of classification according to the research problem. Results.The publication reveals a generalized approach to theoretical developments on the classification of embedded trade enterprises and their incoming groups. Particular attention is paid to the factors of formation of incoming groups of built-in trade enterprises, such as: natural-climatic, ecological, ergonomic, urban, typological, functional-planning, architectural-spatial, structural-technological, socioeconomic, aesthetic (stylistic). Scientific novelty. Characteristic features and a wide range of classification of the built-in enterprises of trade, their development of interaction with development of the market of design and marketing are considered. Practical significance. Classification of embedded trade enterprises - is a contribution to the formation of a holistic picture of the theoretical foundations. Understanding the principles of formation of input groups directly depends on the classification of embedded trade enterprises, so it is of practical importance for the conceptualization of the theoretical basis of modern design and scientific issues related to the study of environmental design.